Influência do sinal filogenético sobre estrutura funcional de assembleias ecológicas : uma abordagem computacional - Nascimento, Erivelton Rosário do (2018)
Understanding the historical-evolutionary mechanisms that govern coexistence patterns at the community level can provide a greater understanding of biodiversity and help clarify key ecology issues about species diversity, composition, and distribution. However, understanding the of species coexistence while ignoring the effect of evolutionary patterns of species’ phenotypes on patterns may be inappropriate, since the assembly of ecological communities’ results from the interaction between ecological and evolutionary processes over time. Therefore, we seek to investigate, through computational simulations, how the evolutionary mode of species characteristics can affect the functional structure of ecological assemblies. Specifically, we investigated the effect of the phylogenetic signal of the functional attribute in the clade on the pattern of functional structure of ecological assemblies under different assemblage assembly rules (environmental filtering, limiting similarity and stochasticity). In addition, we evaluated the statistical performance, through the type I and II error rates, of the NRI and NTI assembly structure metrics. For this, 300 thousand assemblies were simulated at three phylogenetic signal levels (conserved, neutral and labile), three patterns of species occupation and three different assemblage assemblies. We expect clades with phylogenetically conserved traits to determine assemblies of species most likely to exhibit functional clustering patterns, clades with phylogenetically labile trait results in assemblies with a greater tendency to exhibit a functional overdispersion pattern. Finally, clades with traits in neutral evolution - that is, in which the characteristic evolves according to the Brownian motion - determines assemblies guided only by rules of assembly (competition and environmental filter). Our results demonstrated that the way trait evolves does not affect the capacity of NRI and NTI metrics in satisfactorily identifying stochastic processes in assembly community. However, when deterministic assembly rules are imposed, the phylogenetic signal plays an important role in the statistical power of metrics. Therefore, they should be used only when the trait evaluated takes on neutral evolution, and that the evolution through Brownian motion should be taken as an assumption of these metrics when applied to the functional structure.